2008
DOI: 10.1175/2008mwr2273.1
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Hurricane Boundary Layer Small-Scale Coherent Structures

Abstract: Data with high temporal and spatial resolution from Hurricanes Isabel (2003) and Frances (2004) were analyzed to provide a detailed study of near-surface linear structures with subkilometer wavelengths of the hurricane boundary layer (HBL). The analysis showed that the features were omnipresent throughout the data collection, displayed a horizontal and vertical coherency, and maintained an average orientation of 7°l eft of the low-level wind. A unique objective wavelength analysis was conducted, where wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
96
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 23 publications
11
96
2
Order By: Relevance
“…PBL rolls form due to instabilities of the PBL mean state, which is determined by the vertical profiles of the mean horizontal wind vector and the vertical potential temperature (Lilly, 1966;Faller and Kaylor, 1967;Brown 1980;Etling and Brown, 1993;Foster 1996Foster , 2005Young This is why the rolls tend to align along the mean PBL vertical wind shear (Lilly, 1966;Brown 1970Brown , 1972Foster 1996Foster , 2005Foster and Levy, 1998). As mentioned above, Doppler radar analyses show that PBL roll vortices that tend to align close to the surface wind direction and that have subkilometer to multikilometer wavelengths, but nearly always at aspect ratios comparable to those seen in standard rolls, are a frequent feature of the hurricane boundary layer (Wurman and Winslow, 1998;Morrison et al, 2005;Lorsolo et al, 2008;Ellis and Businger, 2010). The dynamical hurricane boundary layer depth can be subkilometer near the storm center, and it tends to increase with increasing radius from the center (Zhang et al, 2011).…”
Section: Standard Pl Anetary Boundary L Ayer Roll Vorticesmentioning
confidence: 86%
“…PBL rolls form due to instabilities of the PBL mean state, which is determined by the vertical profiles of the mean horizontal wind vector and the vertical potential temperature (Lilly, 1966;Faller and Kaylor, 1967;Brown 1980;Etling and Brown, 1993;Foster 1996Foster , 2005Young This is why the rolls tend to align along the mean PBL vertical wind shear (Lilly, 1966;Brown 1970Brown , 1972Foster 1996Foster , 2005Foster and Levy, 1998). As mentioned above, Doppler radar analyses show that PBL roll vortices that tend to align close to the surface wind direction and that have subkilometer to multikilometer wavelengths, but nearly always at aspect ratios comparable to those seen in standard rolls, are a frequent feature of the hurricane boundary layer (Wurman and Winslow, 1998;Morrison et al, 2005;Lorsolo et al, 2008;Ellis and Businger, 2010). The dynamical hurricane boundary layer depth can be subkilometer near the storm center, and it tends to increase with increasing radius from the center (Zhang et al, 2011).…”
Section: Standard Pl Anetary Boundary L Ayer Roll Vorticesmentioning
confidence: 86%
“…Rolls have been reported to frequently occur in the hurricane boundary layer (HBL) in observational studies (Wurman and Winslow 1998;Morrison et al 2005;Lorsolo et al 2008;Zhang et al 2008;Ellis and Businger 2010). Most of the observations were made by Doppler radars during landfalling hurricanes and helped to quantify some characteristics of rolls.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these observations were obtained by Doppler radar from landfalling hurricanes (Wurman and Winslow 1998;Morrison et al 2005;Lorsolo et al 2008;Ellis and Businger 2010). In the radar observations, rolls are detected because they induce organized perturbations in the wind field.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength of rolls estimated from the radar observations is highly variable, ranging from a few hundred meters to a few kilometers. For example, Lorsolo et al (2008) observed rolls in Hurricanes Isabel (2003) and Frances (2004) with wavelengths ranging from 200 to 650 m. Morrison et al (2005) found the majority of rolls during the landfalls of four hurricanes had wavelength in the range 1-2 km. Synthetic aperture radar observations identified rolls with wavelengths of 3-6 km (Katsaros et al 2000).…”
Section: Introductionmentioning
confidence: 99%